A study on Chinese Medicine to alleviate the Adverse Effects of Western Medicine in the Treatment of Lupus Nephritis - Li, Rui; Liu, Chunying (Journal of Contemporary Medical Practice, 2024)
Lupus nephritis (LN) is the most serious and common complication of systemic lupus erythematosus (SLE), which is mainly treated with glucocorticoids combined with immunosuppressive drugs, but its long-term use in large quantities can produce many toxic side effects, which seriously affect the continued application of therapeutic drugs and affect the prognosis and quality of life of patients. TCM can effectively reduce the toxic side effects of western drugs, improve clinical efficacy, reduce comorbidities, ensure the continued use of western drugs, reduce the relapse rate after discontinuation of drugs, and improve the prognosis of patients through evidence-based treatment. The combination of Chinese and Western medicine can effectively control LN activity, relieve symptoms, improve renal function, and reduce the side effects of Western medicine.